Review: Anxiety and Quality of life in Patients with Myocardial Infarction - Panthee, Bimala; Kritpracha, Charuwan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2011)
Obejctive: Anxiety and reduced Quality of Life (QoL) are commonly reported in patients with myocardial infarction (MI) for long years and has a great interest to improve patients’ quality of life. Almost all of the patients with MI will have anxiety to some level. Persistent anxiety for long period has detrimental effect on quality of life. Therefore this study is aimed to find out the effect of anxiety on quality of life of patients with MI.Methods: Published literatures were searched using individual or combination of keywords: anxiety, quality of life and myocardial infarction in following databases: PubMed, CIHNAL, Proquest, and Google Scholar. The full texts were obtained from the journal homepage using Prince of Songkla University and those that could not be accessed from this University were obtained from the University of Tokyo network. Papers which were not accessible from these two networks were excluded from the review.Results: Majority of studies found that patients with MI reported high level of anxiety persisting over months to years affecting QoL. Some studies showed that anxiety was associated with complications and all of the study showed that anxiety was associated with decreased quality of life. Different studies measured anxiety and quality of life differently which might have affect the results of the studies and most of the studies did not consider it and lack to correlate the level of anxiety in each dimension of QoL is noted. High level of anxiety was correlated with the poorer quality of life. Therefore, the researcher should note that which level of anxiety the patient is suffering from because mild anxiety is helpful to focus attention; to learn the stressful situation and solve the problems to protect him/her by themselves. Moderate level of anxiety reduces the patient’s concentration but facilitates to seek information and solve problems with assistance. Severe anxiety results in difficulties in thinking and reasoning and disturbs physiological functioning. Therefore, it is equally important to consider the correlation between mild, moderate anxiety to QoL.Conclusion: Anxiety affects negatively in QoL in patients with MI. Identification of the level of anxiety can help plan effective nursing management of MI patients.